2011
DOI: 10.1103/physrevlett.106.074501
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Surface Permeability with Intracrystalline Diffusivity in Nanoporous Solids

Abstract: The rates of uptake and release of guest molecules in nanoporous solids are often strongly influenced or even controlled by transport resistances at the external surface ("surface barriers") rather than by intraparticle diffusion, which was assumed to be rate controlling in many of the earlier kinetic studies. By correlating the surface resistance with the intracrystalline diffusivity, we develop here a microkinetic model which closely reproduces the experimentally observed results for short-chain alkanes in Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 92 publications
(105 citation statements)
references
References 32 publications
5
99
0
1
Order By: Relevance
“…Previous IFM studies [31][32][33][34][35] have shown that, for many zeolite systems, the sorption kinetics are significantly affected by surface resistance. It was not possible to investigate this aspect in the present study due to the shape of the DDR crystals which precludes accurate measurements close to the external surface.…”
Section: Discussionmentioning
confidence: 99%
“…Previous IFM studies [31][32][33][34][35] have shown that, for many zeolite systems, the sorption kinetics are significantly affected by surface resistance. It was not possible to investigate this aspect in the present study due to the shape of the DDR crystals which precludes accurate measurements close to the external surface.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies 35,36 have shown that the transport resistance of surface barriers results from a total blockage of the pore entrances and that the uptake and release occurs by detours via unblocked pores, which remain fully opened. This means water molecules destroy the MOF structure close to the crystal surface, resulting in blocked pore entrances that have to be bypassed by the guest molecules during the mass transfer, causing the additional mass transfer resistance referred to as surface barriers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we provide a linear fit to the data points by which means we have determined the mean surface permeability to 0.383 m/s and we show also a surface permeability prediction on the basis of the self-diffusion coefficient 43 (crosses). It is furthermore instructive to mention that the corrected diffusivity is identical to the self-diffusion coefficient in the concentration range of Figure S11.…”
Section: S22mentioning
confidence: 99%